Toxicity Effects of Clitoria Ternatea L. Extract in Liver and Kidney Histopathological Examination in Mus Musculus - Khatib, Aulia; -, Tofrizal; Arisanty, Dessy (IIUM Medical Journal Malaysia, 2024)
INTRODUCTION: Clitoria ternatea L. or butterfly pea is more increasingly being consumed as traditional medicine though it contains secondary metabolites, which can be non-beneficial to its consumer. LD50 and histopathological examination are used frequently in toxicity studies. Thus we aimed to determine the toxicity level of Clitoria ternatea L. flower extract and its effects on the liver and kidney in mice. MATERIALS AND METHOD: We carried out this analytical experimental study with from August 2021 to June 2022. Mice were categorised into five dose groups. They were treated with aquades, paracetamol-induced, and flower extract at 500, 1000, and 2000 mg/kg BW orally for 14 consecutive days. RESULTS: C.ternatea flower was classified as having very low toxicity (LD50>2000 mg/kg BW). We detected toxicity signs in mice such as lethargy and tremor in the group treated with more than 1000 mg/kg BW. Histopathological examinations showed leucocytes, vacuolation, and necrosis in the liver and kidneys of mice. There were significant differences in liver and kidney histopathological scores between the five study groups (p<0.05). CONCLUSION: C.ternatea flowers are safe to consume at a dosage of 500 and 1000 mg/kg BW since no mice died after being treated for 14 days. Liver and kidney damage appeared at 2000 mg/kg BW dosage in histopathological examination. Hence, its consumption at this dosage should be limited.